A Study on Impact of AI and ML on Decision-Making Processes and Management Practices within IT Organizations (International Journal of Food and Nutritional Sciences, 2022)
The advent of Artificial Intelligence (AI) and Machine Learning (ML) technologies has revolutionized decision-making processes and management practices within IT organizations. These technologies enable organizations to make data-driven decisions, optimize operations, and enhance customer experiences. This study explores the impact of AI and ML on the decision-making process and management practices in the IT sector. It investigates the integration of AI and ML into management systems, evaluates their effectiveness in strategic decision-making, and identifies both the benefits and challenges these technologies introduce to IT organizations.